Legal Protection for Online Gamers Who Are Victims of Nonverbal Sexual Violence - Sutiawan, Hendrik Agus; Rasjidi, Ira Thania; Nasution, M.Y.F. Hafidz; Hariani, Riri Rezeki; Agung, Mhd. Sutan (Jurnal Penelitian Medan Agama, 2024)
Sexual violence, both physical and non-physical, includes online sexual harassment which is increasing with technological advances. The ITE Law and the TPKS Law regulate victim protection, including in cases of sexual abuse of children through online games. This research focuses on the impact of game addiction on personality and legal protection for victims. This research uses a normative juridical method to analyze laws and regulations related to sexual violence in online games. The legislative approach identifies the role of the TPKS Law in the prevention, handling, and restoration of victims' rights, as well as the effectiveness of regulations with government supervision. Online game addiction can affect the user's character, causing negative effects such as hostility and mental health problems. External factors, such as exposure to media and technology, as well as internal factors, such as psychological problems, contribute to deviant behavior. Online child grooming, which involves manipulation and threats, increases with technological advances, exacerbating child sexual abuse. B. Legal protection for victims of non-verbal sexual violence is increasingly important. The Sexual Offenses Act provides protection, but legal gaps still exist. Electronic-based sexual violence is also regulated with strict penalties. Legal protection for victims of nonverbal sexual violence in online games is essential. Law No. 12 of 2022 and related laws provide the legal basis for legal action.